2017
DOI: 10.1590/1517-869220172304175654
|View full text |Cite
|
Sign up to set email alerts
|

Kinanthropometric Attributes of Elite Male Judo, Karate and Taekwondo Athletes

Abstract: Introduction: It is well known that the body composition of an athlete plays a critical role in sports performance. However, although many studies exist concerning the kinanthropometric attributes of mainstream sports, few studies are forthcoming on individual martial arts disciplines, especially in elite athletes. Objective: This study aimed at establishing the kinanthropometric attributes of Judo, Karate, and Taekwondo athletes. Methods: Thirty-eight elite male Judo (n=42, mean age: 21.7±2.9 years), Taekwond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 13 publications
0
9
2
5
Order By: Relevance
“…Comparing the body fat percentage values of this study to other elite-level athletes of different countries investigated in similar studies, however, shows that our athletes had lower body fat percentage values [16,40,41,56,76]. In contrast, the findings of the present study demonstrated higher values compared with the results of some of the previous studies in elite athletes [26,29,59,63]. Compared to the studies in recreational taekwondo players, our athletes had lower values of body fat percentage [49,72,74].…”
Section: Discussioncontrasting
confidence: 82%
“…Comparing the body fat percentage values of this study to other elite-level athletes of different countries investigated in similar studies, however, shows that our athletes had lower body fat percentage values [16,40,41,56,76]. In contrast, the findings of the present study demonstrated higher values compared with the results of some of the previous studies in elite athletes [26,29,59,63]. Compared to the studies in recreational taekwondo players, our athletes had lower values of body fat percentage [49,72,74].…”
Section: Discussioncontrasting
confidence: 82%
“…There seems to be a trend of body fat percentage increase, as in several studies conducted in other countries, the recent ones reported higher body fat percentages (17). While the body fat percentage of female taekwondo athletes reported in most studies is still below 20%, for male taekwondo athletes, however, the body fat percentage reported in most studies is usually less than that of the females (5,17). For example, Arabaci et al (7) reported that the mean body fat percentage of elite male taekwondo athletes was 7%, which seemed to be gender-dependent.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, anthropometry is recognized as one of the most important tools in examining physical features. Besides, it has been realized that the body composition of the athletes plays a vital role in their sport performance (5), and there are close associations between the body composition attributes and motor performance (6). Arabaci et al (7) also suggested that abatement of body fat percentage and increase of fatfree mass could result in higher VO 2max levels.…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, las diferencias encontradas en este estudio están directamente relacionadas con el tipo de deporte y el entrenamiento especializado de cada modalidad 21 . Esta información obtenida es relevante, puesto que podría usarse no sólo para predecir el éxito del deportista 7 , sino también como criterios pertinentes para relacionar con la salud, así verificó utilizando la prueba de Levene.…”
Section: Discussionunclassified